Penerapan Pembelajaran Kooperatif Tipe Find Someone Who dan Flashcard Game untuk Meningkatkan Motivasi Belajar Siswa - Binti Nurhaniyah; Budi Eko Soetjipto; Fattah Hanurawan (Faculty of Education Universitas Negeri Malang, 2018)
Abstract: The purposes of this classroom action research were to describe: (1) the application of learning cooperative find someone who and flashcard game type to increase learning motivation social studies in students’ fifth grade; and (2) response of fifth grade students SDN Klanderan to the application find someone who and flashcard game. The subjects of this study is the fifth grade students totaling 32 students. This study was conducted in one cycle. Data collection instruments in this study used observations, questionnaires, and interviews. Data analysis techniq used qualitative descriptive. Conclusion the results of this study were: (1) learning motivation social studies in fifth grade students SDN Klanderan improved with the achievement of the aspect of hope of success, persistence of effort in learning, as well as the ability to face and overcome the failures of learning; and (2) students of the fifth grade SDN Klanderan responded with pleasure, passion thinking, and agrees. Abstrak: Tujuan penelitian tindakan kelas ini adalah untuk mendeskripsikan (1) penerapan pembelajaran kooperatif tipe find someone who dan flashcard game untuk meningkatkan motivasi belajar IPS siswa kelas V; (2) respons siswa kelas V SDN Klanderan terhadap penerapan find someone who dan flashcard game. Subyek penelitian ini adalah siswa kelas V yang berjumlah 32 siswa. Penelitian dilakukan dalam satu siklus. Alat pengumpul data dalam penelitian ini menggunakan observasi, angket, dan wawancara. Teknik analisis data hasil penelitian ini menggunakan deskriptif kualitatif. Kesimpulan hasil penelitian ini adalah: (1) motivasi belajar IPS siswa Kelas V SDN Klanderan meningkat ditandai dengan tercapainya aspek harapan keberhasilan, ketekunan usaha dalam belajar, serta kesanggupan menghadapi dan mengatasi kegagalan belajar; dan (2) siswa kelas V SDN Klanderan merespons dengan senang, semangat berpikir, dan setuju.